Planetary rock-breaking bodies and horizontal drilling - V. L. Skripka; L. H. Minyazeva (Известия высших учебных заведений: Геология и разведка)
Background. The article considers one of the variants of the original planetary drilling organ, in which used multiple impacts on the mass to be destroyed. This makes it possible to improve the methods of sinking inclined and horizontal wells by significantly reducing the required feed force and reducing the energy intensity of bottom hole destructionAim. To investigate drilling methods and tools, which can be used to significantly reduce the radius of changes in drilling direction when creating inclined and horizontal wellbores.Materials and methods. An analysis of patent information and its experimental verification under laboratory conditions.Results. The main advantage of the analyzed drilling bodies is associated with their rock-breaking ability due to multiple shock pulses directed at an angle to the face surface. This allows the energy intensity of fracture and the required feed force in the axial direction to be significantly reduced, thus providing for larger wellbore diameters. A reduction in the axial length of the drilling body leads to a decrease in the radius of changes in drilling direction, thereby contributing to improved technologies of wellbore drilling, in particular, when creating horizontal wellbores.Conclusion. Planetary rock-breaking bodies implement quasi-dynamic rock destruction by multiple shock pulses and spalling off rock pieces from an automatically formed wavy face surface. On this basis, modern technologies of drilling inclined and horizontal wellbores can be improved.